Patient and caregiver agreement on prognosis estimates for older adults with advanced cancer. Issue 1 (9th October 2020) - Loh, Kah Poh; Soto Pérez de Celis, Enrique; Duberstein, Paul R.; Culakova, Eva; Epstein, Ronald M.; Xu, Huiwen; Kadambi, Sindhuja; Flannery, Marie; Magnuson, Allison; McHugh, Colin; Trevino, Kelly M.; Tuch, Gina; et al.
Abstract : Background: Disagreements between patients and caregivers about treatment benefits, care decisions, and patients' health are associated with increased patient depression as well as increased caregiver anxiety, distress, depression, and burden. Understanding the factors associated with disagreement may inform interventions to improve the aforementioned outcomes. Methods: For this analysis, baseline data were obtained from a cluster‐randomized geriatric assessment trial that recruited patients aged ≥70 years who had incurable cancer from community oncology practices (University of Rochester Cancer Center 13070; Supriya G. Mohile, principal investigator). Patient and caregiver dyads were asked to estimate the patient's prognosis. Response options were 0 to 6 months, 7 to 12 months, 1 to 2 years, 2 to 5 years, and >5 years. The dependent variable was categorized as exact agreement (reference), patient‐reported longer estimate, or caregiver‐reported longer estimate. The authors used generalized estimating equations with multinomial distribution to examine the factors associated with patient‐caregiver prognostic estimates. Independent variables were selected using the purposeful selection method. Results: Among 354 dyads (89% of screened patients were enrolled), 26% and 22% of patients and caregivers, respectively, reported a longer estimate. Compared with dyads that were in agreement, patients were more likely to report a longer estimate when they screened positive for polypharmacy (β = 0.81; P = .001), and caregivers reported greater distress (β = 0.12; P = .03). Compared with dyads that were in agreement, caregivers were more likely to report a longer estimate when patients screened positive for polypharmacy (β = 0.82; P = .005) and had lower perceived self‐efficacy in interacting with physicians (β = −0.10; P = .008). Conclusions: Several patient and caregiver factors were associated with patient‐caregiver disagreement about prognostic estimates. Future studies should examine the effects of prognostic disagreement on patient and caregiver outcomes. Abstract : Nearly one‐half (48%) of older patients and caregivers disagree with each other about the patient's prognosis; specifically, 26% of patients and 22% of caregivers report a longer estimate of the patient's prognosis. Caregiver distress, patient communication self‐efficacy, polypharmacy, and oncologist sex are associated with patient‐caregiver agreement about prognostic estimates.